Studies of The Graft of Ashouri and Nab AL Jamal Varieties With The Major Rootstocks (Journal of Hama University, 2020)
This research was implemented in the nursery of the agricultural department in Hama during (2012, 2013, 2014). We have used to rootstocks, The results showed that the Ashouri rootstocks exceeded P. Atlantica significantly in regard of the percentage of seedling. Ashouri rootstock was (80%) and P. Atlantica rootstock was (42.5%). The Ashouri rootstocks outperformed the P. Atlantica rootstocks in the number of the two- year plants which could be used for grafting. The average percentage of the budding from Ashouri and P. Atlantica  rootstocks were (69, 61 %) respectively. Pistachio varieties (Ashouri, Nab AL Jamal) which were budded on the Ashouri rootstocks exceeded the P. Atlantica rootstock. The average ratio of successful  graft of Ashouri variety budded on the (Ashouri, P Atlantica) rootstocks reached (73.00, 30.50 %) respectively, The average amount of successful graft of Nab AL Jamal variety budded on the (Ashouri, P. Atlantica) rootstocks reached (64.50, 21.00 %) respectively.